A Hyperelastic Constitutive Model for Chain-Structured Particle Reinforced Neo-Hookean Composites. (5th April 2016) - Guo, Zaoyang; Chen, Yang; Wan, Qiang; Li, Haitao; Shi, Xiaohao; Tang, Shan; Peng, Xiongqi
Abstract: A hyperelastic constitutive model is proposed to predict the mechanical behavior of macroscopically transversely isotropic composites containing chain-structured particles. In this model, each particle chain is treated as a "virtual fiber" and the composite is modeled as a virtual fiber reinforced composite. When the particles and the matrix are both neo-Hookean materials, the virtual fiber, which is a particle-reinforced composite itself, is modeled as a neo-Hookean material and its effective stiffness is predicted by the classical three phase model. A simple method is developed to construct the virtual fibers and the corresponding virtual fiber-reinforced model is derived for the chain-structured particle reinforced composite. The representative volume element models are created to verify the virtual fiber transformation and the constitutive model numerically. The effects of the microstructure, the disturbance of particle locations, and the choice of the virtual fibers are investigated. The numerical results show that the proposed virtual fiber reinforced composite model can well predict the mechanical responses of the composites with chain-structured particles. Graphical Abstract: Highlights: A hyperelastic constitutive model is proposed to predict the mechanical behavior of macroscopically transversely isotropic composites containing chain-structured particles. In this model, each particle chain is treated as a "virtual fiber" and the composite is modeled as a virtual fiber reinforced composite. The representative volume elements (RVE) models are created to verify the constitutive model and the numerical results agree well with the predictions of the model. The effects of the microstructure, the disturbance of particle locations, and the choice of the virtual fibers are discussed in detail.